Rethinking the Binary of Pure Objectivity and Relativistic Chaos - Huber, Jason (Stance: an international undergraduate philosophy journal, 2019)
This paper seeks to refute some of the common presuppositions of traditional Western epistemologies, which center on the claim that subjectivity cannot be as truth-yielding as "objectivity." This paper argues that aspects of the subjective can effectively be utilized in a valid epistemology attempting to approach an understanding of the truth of lived human experience—i.e. that subjectivity can in certain circumstances be as truth-yielding as, or even more so than, the epistemic ideal of objectivity. Ultimately, this paper concludes that the objective-subjective epistemic binary is artificial and disadvantageous in that neither pure objectivity nor absolute relativity are possible.